IbM PEMBERIAN NUTRISI BRAIN BOOSTER PADA IBU HAMIL - Fitriyani Fitriyani; Risqi Dewi Aisyah; Suparni Suparni (Universitas Muhammadiyah Semarang, 2017)
The nutrient intake during pregnancy results in the inability of the born child to learn and adapt to the demands of society for the abilities that are considered normal. IbM Activities Brain nutrition during pregnancy is expected to improve the brain's quality in the fetus so as to enable an increased potential for post-child intelligence (Depkes, 2009). This activity is done by providing information to pregnant women about the importance of brain booster nutrition during pregnancy, brain booster nutrition and empowerment of cadres in monitoring the nutritional consumption of brain booster during pregnancy. Activity time in March-August 2017. Place of activity in working area of Kedungwuni II Public Health Center , Kedungwuni I Publich Health Center and Buaran Health Center. The results of the activity there is an increase in knowledge of pregnant women about brain booster before and after being given counseling, pregnant women consume regular brain booster nutrients. It is necessary to provide information on nutrition of brain booster and nutrition monitoring during pregnancy by cadre continuously so that pregnant mother does not experience malnutrition.Keyword: Nutrition, Brain booster, Pregnant women